A literatura infantil no desenvolvimento da linguagem - David, Rosa de Oliveira Penha (Universidade Federal do Tocantins, 2023)
The present research proposes to study Children’s Literature in the development of language, taking into account in that literature is of paramount importance in the formation of the individual, in the formation of the reader and in writing. This bibliographic research sought to understand how children’s literature contributes to the acquisition of reading and writing, in the Early Years of Elementary School. In this way, we will see how children’s literature can contribute to the process of acquiring reading and writing for children who are being literate. Considering the importance of literature, we empahasize that we are not talking about using it as an apparatus for teaching syllables, words and sentences, but rather as an instrument for the developmente of children’s language. For this, we also seek to characterize Children’s Literature and its role in the child’s learning process; understand the concepts of language that support the teaching of reading and writing, understand the role of Children’s Literature as a mediator of Knowledge and as a constituent of the subject and identify the discursive forms of dialoguing with Children’s Literature in literacy. We seek theoretical support from the authors, Backhtin (2000), Geraldi (2011), Vygotsky (2007) and Smolka (2012), who talk about the the concepts of language and literacy that support teaching practice. Authors Roxane Rojo (2015), Abramovich (1997), Colomer (2017) talk about the possibilities of literature as a way for children to discover other places and open the door to the human imagination. Considering the importance of how and when to use Children’s Literature opened up possibilities for structuring this research proposal. Trying to understand wha children’s literature represents inside and outside the classroom and how it has been worked on, impels us to reflect on the topic discussed.